Power and energy management of multiple energy storage systems in electric vehicles - Rosario, L C (Cranfield University, 2008)
This dissertation contributes to the problem description of managing power and energy of multiple energy sources for electric vehicle power system architectures. The area of power and energy management in the application domain of electric vehicles is relatively new and encompasses several different disciplines. Primarily, the challenges in electric vehicles having multiple energy storage systems lies in managing the energy expenditure, determining the proportional power splits and establishing methods to interface between the energy systems so as to meet the demands of the vehicle propulsion and auxiliary load requirements. In this work, an attempt has been made to provide a new perspective to the problem description of electric vehicle power and energy management. The overall approach to the problem borrows from the basic principles found in conventional management methodology. The analogy between well-known hierarchical management concepts and power and energy management under timing constraints in a general task-graph is exploited to form a well-defined modular power and energy management implementation structure. The proposed methodology permits this multidisciplinary problem to be approached systematically. The thesis introduces a modular power and energy management system (MPEMS). Operation of the M-PEMS is structured as tri-level hierarchical process shells. An Energy Management Shell (EMS) handles the long-term decisions of energy usage in relation to the longitudinal dynamics of the vehicle while processes within a Power Management Shell (PMS) handles the fast decisions to determine power split ratios between multiple energy sources. Finally, a Power Electronics Shell (PES) encompasses the essential power interfacing circuitry as well as the generation of low-level switching functions. This novel framework is demonstrated with the implementation of a power and energy management system for a dual-source electric vehicle powered by lead acid batteries and ultracapacitors. A series of macro simulations of the energy systems validated against practical tests were performed to establish salient operating parameters. These parameters were then applied to the M-PEMS design of a demonstrator vehicle to determine both the general effectiveness of a power and energy management scheme and to support the validity of the new framework. Implementation of the modular blocks that composes the entire system architecture is described with emphasis given to the power electronics shell infrastructure design. The modular structure approach is design-implementation oriented, with the objective of contributing towards a more unified description of the electric vehicle power and energy management problem.